STUDI FENOMENOLOGI: ANOMALI HIDUPKU DI DALAM PENJARA - Indari Indari (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: Adolescents as prison will face psychological challenges such as stigma, discrimination, isolation and instability. The purpose of the study was to explore the meaning of life of adolescents as prison. Methods: This research was a Qualitative research used interpretive phenomenology approach. This research was conducted at the Malang Correctional Center. Participants in this study were seven adolescents with purposive sampling technique. In-depth interviews are used to obtain data and data analysis using IPA (interpretative Phenomenological Analysis). Results: Nine major research themes were found, namely fear of being overshadowed by past mistakes and shame as a former prisoner, feeling ostracized and getting a bad label from the community, chaotic when returning to society, feeling humiliated and failing as a former prisoner, feeling valuable and trying to be better, getting care from parents, family and society, still being able to play a role and being needed by others, hoping to become a successful person, challenged to improve themselves. Conclusion: Adolescents as ex-prisoners experience a transition period, namely psychological problems including feelings of being ostracized, getting stigmatized by society, feeling inferior and worthless. Support from the closest people and community acceptance causes former prisoners to be able to play a role in society, causing former prisoners to return to the community. Keywords: Adolescent, ex-convict, psychological